Through the genetic bottleneck : O. rufipogon as a source of trait-enhancing alleles for O. sativa - McCouch, Susan R.; Sweeney, M; Li, J; Jiang, H.; Thomson, M.; Septiningsih, E.M.; Edwards, J.; Moncada, P; Xiao, J.; Garris, AJ; Tai, T; Martínez Racines, César Pompilio; et al. (Springer, 2007)
This paper summarizes results from a decade of collaborative research using advanced backcross (AB) populations to a) identify quantitative trait loci (QTL) associated with improved performance in rice and to b) clone genes underlying key QTLs of interest. We demonstrate that AB-QTL analysis is capable of (1) successfully uncovering positive alleles in wild germplasm that were not obvious based on the phenotype of the parent (2) offering an estimation of the breeding value of exotic germplasm, (3) generating near isogenic lines that can be used as the basis for gene isolation and also as parents for further crossing in a variety development program and (4) providing gene-based markers for targeted introgression of alleles using marker-assisted-selection (MAS). Knowledge gained from studies examining the population structure and evolutionary history of rice is helping to illuminate a long-term strategy for exploiting and simultaneously preserving the well-partitioned gene pools in rice.